Differential taxation and firms' financial leverage: Evidence from the introduction of a flat tax on interest income - Frank Fossen; Martin Simmler (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2012)
Tax competition for the mobile factor capital has led to a trend in many countries to levy lower taxes on interest income, often introducing differential taxation between interest and business income. In this study, we analyze the effect of such differential taxation on the debt ratio of firms. We exploit a 2009 tax reform in Germany as a quasi-experiment, which introduced a flat final withholding tax and opened a gap of 18 percentage points between the tax rate on income from unincorporated businesses and the new lower tax rate on interest income. We apply a regression adjusted semi-parametric difference-in-difference matching strategy based on firm level panel data. In addition, we implement a more structural approach with a tax rate differential, taking into account its endogeneity by using instrumental variables. The results indicate that firms increase their leverage when the tax rate on interest income decreases, albeit to a small degree.
Keywords: H25; H24; G32; 330; income taxation; capital taxation; financial structure; leverage; matching; Kapitalertragsteuer; Flat Tax; Unternehmensbesteuerung; Einkommensteuer; Steuerwirkung; Kapitalstruktur; Schätzung; Deutschland